Phenotypic Architecture and Genetic polymorphims Associated with Social Behaviour in Zebra fish - Da Cruz Gonçalves, Cláudia Cristiana (2022)
"Social behaviour is fundamental for the survival and reproduction of organisms, and most animals are social to some degree. It is generally recognized that many neuropsychiatric diseases are associated with some form of social deficit or are accompanied by social impairments. There is also evidence that actual and perceived social isolation are both related with increased mortality risk. Given that social behaviour is central in both humans and other animals’ lives, many researchers with different backgrounds have been actively engaged in the challenge of understanding the nature of this highly complex and dynamic phenomenon. Social behaviour that independently evolved multiple times across animals is an extremely diverse behavioural category, influenced by multiple factors (genes, hormones, environment, ecology, development, life history trait, etc.) requiring a multidisciplinary approach, integrative analysis and standardized terminologies. However, despite its great diversity (both between and within species), there are similarities namely at mechanistic and functional level, which allows organizing social behaviours in functional modules, similar to those used in gene ontology categories. "